Evaluasi kebijakan pembangunan daerah di Provinsi Jawa Tengah - Syukri, Agus Fanar; Widiastuti, Wiwin (Publisia: Jurnal Ilmu Administrasi Publik, 2021)
National and regional development to improve the economy and people's welfare is carried out with a sustainable concept based on natural resources and with an environmental perspective. To accelerate regional development in Central Java Province, Presidential Regulation number 79 of 2019 has been issued by setting 3 areas in Central Java as a focus, namely Bregasmalang, Kedungsepur and Purwomanggung and 5 other areas as supporting areas. To find out the results of regional development in all cities and districts in Central Java, a regional competitiveness index (RCI) was measured in 2019. From comparing the results of RCI in 3 focus areas and 5 supporting areas, it turns out that the RCI in the focus areas is not higher value than the supporting areas, Bregasmalang 5.86 was lower than Barlingmascakep 6.09; Purwomanggung 4.87 was lower than Subosukowonosraten 5.20, indicating that the policy to determine 3 areas for accelerated development of the region of Central Java Province is not fully evidence- based. The recommendation is that the policy for regional development in Central Java Province in the future is based more on evidence, the results of RCI.